TINJAUAN PERTANGGUNGJAWABAN PELAKU TINDAK PIDANA PORNOGRAFI MENURUT UNDANG-UNDANG NOMOR 44 TAHUN 2008 TENTANG PORNOGRAFI - sinaga, erinda; R, mukhlis; erdiansyah, erdiansyah (FIAT JUSTISIA, 2014)
Pornography has damaged morale of Indonesian people, especially the youth. Pornography happens must have a lot of special attention, especially the enforcement of law and community to cooperate in fighting the pornography. Pornography has been enacted in the Law Number 44 of 2008 on pornography, but has not been able to give the benefit of addressing pornography crimes, because the Law still has a weakness in the system of criminal responsibility and overlap with the ideas such as producing, reproducing for copying, distributing and reselling. Theres also a weakness in determining the criminal related to Article 8, 9, and 11 of Pornography Laws, the lack of definition of the word "download" with regard to article 5, that no one is allowed to lend or download pornography as referred to in Article 4 verse (1). Of these weaknesses affect criminal responsibility in the acts of pornography.Â Keywords: Obligation, Crime, Pornograhphy.Â